2012
DOI: 10.1590/s1983-40632012000300005
|View full text |Cite
|
Sign up to set email alerts
|

Doses de zinco e nitrogênio na produtividade e qualidade de grãos de ervilha

Abstract: INTRODUÇÃOOriginária do Oriente Médio, a ervilha é muito apreciada em todo o mundo, sendo consumida como grãos verdes ou enlatados (secos reidratados ou verdes). No Brasil, até a década de 1980, o produto era importado, mas, atualmente, a demanda é atendida pela produção nacional. Seu cultivo é efetuado durante o inverno, sendo a planta bastante tolerante a baixas temperaturas (IAC 2009 Zinc and nitrogen doses on pea grains quality and yield Peas present a potential to be cultivated in the winter, in Brazil, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…For the variables number of pods per plant and mass of pods per plant, no data were found in the literature on the estimation of plot size to evaluate these variables, leading to a wide variation in plot sizes used in the work with the crop. The plot sizes used by Cardoso et al (2012); Santos, Cunha, Taira, Souza, and Leal (2018); Singh et al (2019);and Zhang et al (2016) ranged from 10 to 420 plants per plot, which were higher than those obtained in the present study, thus indicating greater reliability in the published information. However, Carvalho, Rezende, Aquino, Freitas, and Oliveira (2012); Garcia, Ferreira, Figueiredo, and Santos (2010); Mahieu et al (2009); and Oliveira, Carvalho, Rezende, and Freitas (2011) used a plot size ranging from one to six plants; these values are below what was estimated in the present study and may have led to less experimental precision in these works.…”
Section: Plot Sizecontrasting
confidence: 64%
See 1 more Smart Citation
“…For the variables number of pods per plant and mass of pods per plant, no data were found in the literature on the estimation of plot size to evaluate these variables, leading to a wide variation in plot sizes used in the work with the crop. The plot sizes used by Cardoso et al (2012); Santos, Cunha, Taira, Souza, and Leal (2018); Singh et al (2019);and Zhang et al (2016) ranged from 10 to 420 plants per plot, which were higher than those obtained in the present study, thus indicating greater reliability in the published information. However, Carvalho, Rezende, Aquino, Freitas, and Oliveira (2012); Garcia, Ferreira, Figueiredo, and Santos (2010); Mahieu et al (2009); and Oliveira, Carvalho, Rezende, and Freitas (2011) used a plot size ranging from one to six plants; these values are below what was estimated in the present study and may have led to less experimental precision in these works.…”
Section: Plot Sizecontrasting
confidence: 64%
“…The plot sizes used by Cardoso et al. (2012); Santos, Cunha, Taira, Souza, and Leal (2018); Singh et al. (2019); and Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Tomm et al (2003) found grain yield of 1,435 kg ha -1 with 'Maria' cultivar. Cardoso et al (2012), while evaluating nitrogen doses application (0-240 kg ha -1 ), found the highest grain yield for 'Utrillo' with the lowest N doses. In addition, Noworolnik & Dworakowski (2010), while studying barley, oat and field pea mixed planting and nitrogen doses (0-50 kg ha -1 ), observed that nitrogen dose increase reduced pea yield.…”
Section: ------------------------------(Cm) -------------------------mentioning
confidence: 95%
“…In excess, N application may be harmful. Therefore, correct application is necessary to avoid excessive leaf area increase, as it may cause self-shading, reducing photosynthetic efficiency and transpiration (Cardoso et al, 2012). In addition, N constitutes amino acids, proteins, enzymes and coenzymes, nucleic acids, vitamins, glycoproteins, lipoproteins, pigments and secondary products (Malavolta, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors (Kaya & Higgs, 2001;Anwaar et al, 2015;Roosta et al, 2018) reported that the decrease in chlorophyll content may be caused by both zinc deficiency and toxicity. Because, zinc is directly involved with the process of photosynthesis, nitrogen metabolism, respiration, and protein synthesis in plants (Malavolta, 2006;Cardoso et al, 2012;Mascarenhas et al, 2014). The cultivar Thaís had more Zn absorption, hence more Zn content in the leaves (Figure 1B).…”
Section: Agronomic Traits Of Curly Lettuce Submitted To Zinc Biofortificationmentioning
confidence: 99%